Effect of size and shape of electrodes on the performance of EDM - Khan, Ahsan Ali; Haque, Md. Mohafizul; Ali, Mohammad Yeakub (2008)
In the present study the effect of size and different shapes of electrodes on material removal rate (MRR), job surface finish and wear ratio (WR) during EDM has been investigated. The work material taken was mild steel and the electrode material taken was copper. The size of the electrodes was 9mm, 15 mm, 20 mm and 30 mm in diameter. The shapes of the electrodes were square, round, triangular and diamond, having the same area of cross-section. The highest MRR was found for round electrodes followed by square, triangular and diamond shaped electrodes. MRR was found to increases sharply with the increase in diameter of the electrodes. With increase in current, the sparks produced are of higher thermal energy. As a result, increase in current resulted increase in MRR. A higher thermal energy also erodes more material from the electrode. Electrode wear (EW) was measured along the crosssection of the electrode as well as along its length. EW was also found to increase with the increase in current. However, the highest EW was fond on the diamond shaped electrodes followed by triangular, square and the round shaped ones. An electrode of smaller cross-section exhibited a higher electrode wear. Wear ratio (WR) was calculated as the ratio of the volume of material removed from the electrode to the same removed from the work material. The highest WR was found on the diamond shaped electrodes followed by triangular, square and round electrodes. It was also found that WR decreases with increase in cross-sectional area of the electrode. Job surface roughness was found to decrease with increase in electrode diameter, but the effect is very insignificant. The smoothest job surface finish was found for round electrodes followed by square, triangular and diamond shaped electrodes. But again, the influence of the shape of the electrodes on job surface finish was found to be insignificant.